The 57th Open Seminar on Acoustics OSA’2010 Gliwice, Poland, September 20 – 24, 2010 - Roman BUKOWSKI (Archives of Acoustics, 2013)
Traditionally you are invited to acquaint with some abstracts of lectures, submitted for presentation in 57th Open Seminar on Acoustics (OSA'10). This national Seminar, with some foreign guests, in this year is organized by Upper Silesian Division of the Polish Acoustical Society, with cooperation of Institute of Physics - Science-Didactics Center at Silesian University of Technology and Acoustics Committee of Polish Academy of Sciences. In this year OSA'10 will take place in Gliwice at the Congress-Educational Center of the Silesian University of Technology. The conference has two famous honorary patrons - the Magnificence Rector of the Silesian University of Technology, Prof. Andrzej Karbownik, and Ministry of Science and Higher Education, Prof. Barbara Kudrycka. The Seminar is a forum for all fields of acoustics. Particularly in this year, in the Seminar Program you can find the following topics: general acoustics, environmental acoustic, biomedical acoustics, acoustics in blind person's life, active noise control, acoustical emission, vibroacoustics, ultrasound, interior acoustics and others. During the Seminar, the theoretical works, experimental, measuring, technical, applied and normative ones are presented. All the lectures prepared for OSA'10 are published in the "57th Open Seminar on Acoustics Materials" - in book form and on cd. This publication is intended for participants of the Seminar and for many libraries in Poland. After acceptation by reviewers, the extended form of some lectures will be published in Archives of Acoustics. Once again we have decided to organize this conference, taking into account the fact that it is an important event for acousticians and other Polish and foreign scientists. We hope that this conference program will gain acceptance and respect among its potential participants. We count on your numerous response and active participation. The Seminar is traditionally sponsored by the Ministry of Science and Higher Education. Further information about OSA'10 you can find at http://ogpta.polsl.pl/osa.